Assessment of Knowledge and Usage Practices of Retinol-Containing Facial Skincare Products Among Medical Students at Baiturrahmah University - Irma Primawati; Olivia Putri; Irdawaty Izrul; Fitra Deny; Rendri Bayu Hansah (Scientific Journal, 2026)
Background: Retinol, a derivative of vitamin A belonging to the retinoid class, is widely used in facial skincare products due to its efficacy in the management of acne and prevention of premature skin aging. The increasing utilization of retinol among medical students necessitates adequate knowledge and appropriate usage practices to minimize potential adverse effects. Objective: To evaluate the level of knowledge and usage practices of retinol-containing facial skincare products among medical students at Baiturrahmah University. Methods: A descriptive cross-sectional study was conducted involving 64 medical students from the Faculty of Medicine, Baiturrahmah University. Participants were recruited using a consecutive sampling technique. Data were collected through a structured questionnaire and analyzed descriptively. Results: The majority of respondents demonstrated a good level of knowledge regarding retinol. Female students exhibited a higher proportion of good knowledge (67.2%) compared to male students. Based on age distribution, respondents aged 21 years showed the highest level of knowledge (62.5%). Appropriate retinol usage practices were predominantly observed among female students (68.1%) and respondents aged 21 years (70.2%). Conclusion: Medical students at the Faculty of Medicine, Baiturrahmah University generally demonstrate good knowledge and appropriate usage practices regarding retinol, with a predominance among female students and those aged 21 years.